Comparative analysis of psycho-pharmacological and psychotherapeutic correction of dyssomnic disorders in military services - Guk Галина (Psychosomatic Medicine and General Practice, 2019)
In the context of the mental health of the military services of the Armed Forces of Ukraine, our attention is drawn to the high prevalence of sleep disorders, which are found in 74-92% of patients of Zaporizhzhia military hospital undergoing inpatient care. Developed at the Department of Psychiatry, Psychotherapy, General and Medical Psychology, Narcology and Sexology of Zaporizhzhia State Medical University, the technique of rapid autogenous correction of dyssomnic syndrome is an attractive alternative to psychopharmacological treatment. We present intermediate results of clinical approbation of the psychotechnique in comparison with the medical treatment which testifies its effectiveness in regulating sleep disorders and overcoming daytime drowsiness in the specified contingent of patients. This is a conference abstract from the II Scientific-practical conference "Psychosomatic medicine: science and practice". It is dedicated to comparative analysis of psycho-pharmacological and psychotherapeutic correction of dyssomnic disorders in military services.